2021
DOI: 10.35366/103314
|View full text |Cite
|
Sign up to set email alerts
|

Fractura de cadera en el adulto mayor: epidemiología y costos de la atención

Abstract: Fractura de cadera en el adulto mayor: epidemiología y costos de la atención

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
(18 reference statements)
0
3
0
2
Order By: Relevance
“…En la serie presentada se encontró que el mayor porcentaje de pacientes con FC fueron mujeres mayores de ochenta años. La distribución por sexo y grupo de edad fue similar a lo presentado por Pech cuando analizó 16 829 pacientes en México (14) . Sin embargo, en el Perú, Palomino y col. evaluaron 79 pacientes y encontraron una población menos envejecida (edad media de 66 años con un rango intercuartílico entre 65 -81) (15) .…”
Section: Discussionunclassified
“…En la serie presentada se encontró que el mayor porcentaje de pacientes con FC fueron mujeres mayores de ochenta años. La distribución por sexo y grupo de edad fue similar a lo presentado por Pech cuando analizó 16 829 pacientes en México (14) . Sin embargo, en el Perú, Palomino y col. evaluaron 79 pacientes y encontraron una población menos envejecida (edad media de 66 años con un rango intercuartílico entre 65 -81) (15) .…”
Section: Discussionunclassified
“…In our study, the male patients accounted for less, that was about 33.5%. Previous studies on hip fracture also showed that the proportion of males was relatively low, about 21%–27% 30,31 . Whether gender was a risk factor for death remained controversial 32 .…”
Section: Inflammation Predict Long‐term Mortality After Hip Fracture ...mentioning
confidence: 99%
“…Hip fracture is a common type of fracture in older people[ 1 ]. Traditional conservative treatment is prone to delay healing and cause muscle atrophy, joint stiffness, and other problems, seriously affecting the quality of life of elderly patients[ 2 ]. With the improvement of modern surgical technology, an increasing number of elderly patients with fractures choose surgical treatment[ 3 ].…”
Section: Introductionmentioning
confidence: 99%